Why Denominations Can Climb Hills: RLDS Conversions in Highland Tribal India and Midwestern America, 1964–2000. Issue 3 (September 2020) - Howlett, David J.
Abstract : Based on oral history interviews and archival sources, this essay analyzes the religious affiliation between Sora villagers in the highlands of eastern India with Reorganized Church of Jesus Christ of Latter Day Saints (RLDS) members in the American Midwest. The relationship between these distinct groups transposed a pattern of interactions between highlands and lowlands in upland Asia to a new globalized space in the late twentieth century. Conceiving of "conversion" as a broad analytic trope to discuss various individual, group, and organizational transformations, this essay argues that "converts" in the Sora highlands and American plains instrumentalized their relationships with the other for their own ends. In the Americans, the Sora found a new patron for long-standing client-patron relationships between highlands people and valley people. In the Sora, the Americans found an "indigenous other" who could be used to justify reforms within their local church body along more cosmopolitan lines. As an upshot of these interactions, Sora and Americans effectively reterritorialized older patterns of "hills" and "valleys" that had been deterritorialized by state-sponsored modernization. Thus, the hills and valleys of upland Asia found a surprising afterlife within the space of a global Christian denomination.